Out-of-vehicle time-of-arrival-based localization in ultra-wide band - Pavel Kukolev; Aniruddha Chandra; Tomáš Mikulášek; Aleš Prokeš (International Journal of Distributed Sensor Networks)
The article presents out-of-vehicle channel measurement results in ultra-wide band spanning 3–11 GHz bandwidth using a vector network analyzer for localization applications. Experiments for different distances and different angles around the parked car are carried out. From the power delay profiles, the distance between the antennas is calculated exploiting the linear dependence of distance with line-of-sight delay peak. The coordinates of a transmitting antenna are found with the help of two receiving antennas following a two-dimensional time-of-arrival-based localization technique. A comparison of the calculated coordinates with the original exhibits an error of less than 6% which establishes the suitability of the proposed approach in locating other neighboring cars.